2005
DOI: 10.1111/j.1471-4159.2005.03576.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel β‐secretase inhibitor KMI‐429 reduces amyloid β peptide production in amyloid precursor protein transgenic and wild‐type mice

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the accumulation of amyloid plaques and neurofibrillary tangles in the brain. The major component of the plaques, amyloid b peptide (Ab), is generated from amyloid precursor protein (APP) by b-and c-secretase-mediated cleavage. Because b-secretase/beta-site APP cleaving enzyme 1 (BACE1) knockout mice produce much less Ab and grow normally, a b-secretase inhibitor is thought to be one of the most attractive targets for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 38 publications
4
114
1
Order By: Relevance
“…The structural requirements for binding also impart high susceptibility to P-glycoprotein (P-gp) transport, thus reducing brain concentrations of BACE-1 inhibitors (Mahar Doan et al, 2002). A few BACE1 inhibitors have been shown to lower brain A␤ levels after direct intracranial administration (Asai et al, 2006;Nishitomi et al, 2006;Sankaranarayanan et al, 2008) or via peripheral administration at relatively high doses in murine models (Chang et al, 2004;Stachel et al, 2006;Hussain et al, 2007;Stanton et al, 2007). However, the lack of potent inhibitors that also possess good pharmacokinetic and brain penetration properties have prevented evaluation of BACE1 inhibitors in larger animals, such as nonhuman primates.…”
mentioning
confidence: 99%
“…The structural requirements for binding also impart high susceptibility to P-glycoprotein (P-gp) transport, thus reducing brain concentrations of BACE-1 inhibitors (Mahar Doan et al, 2002). A few BACE1 inhibitors have been shown to lower brain A␤ levels after direct intracranial administration (Asai et al, 2006;Nishitomi et al, 2006;Sankaranarayanan et al, 2008) or via peripheral administration at relatively high doses in murine models (Chang et al, 2004;Stachel et al, 2006;Hussain et al, 2007;Stanton et al, 2007). However, the lack of potent inhibitors that also possess good pharmacokinetic and brain penetration properties have prevented evaluation of BACE1 inhibitors in larger animals, such as nonhuman primates.…”
mentioning
confidence: 99%
“…Consequently, we designed in a tetrazole moiety, 1H-tetrazole-5-carbonyl, as a bioisostere of the P4-free carboxylic acid of the oxalyl group, and synthesized compound 27 (KMI-429) that exhibited improved stability while maintaining high inhibitory potency. While in-vitro HEK293 cell assays revealed that pentapeptide 27 (KMI-429) dose-dependently inhibited sAPPb production, in-vivo injections of compound 27 into the hippocampus of APP wild type and transgenic Tg2576 mice, respectively, inhibited both amyloid-b production and release of sAPPb in both models [85]. Our docking simulation study showed that KMI-429 was optimized to bind to the active site of BACE1, as shown in Fig.…”
Section: B-secretase Inhibitorsmentioning
confidence: 99%
“…Recent progress in the understanding of the pathology of Alzheimer disease has made it possible for potential disease-modifying therapies to be tested in clinical trials. [7][8][9][10][11] However, no such therapy is available at present. Therefore, cholinergic enhancement remains the most effective therapeutic method to treat AD.…”
Section: Treatment Of Alzheimer's Diseasementioning
confidence: 99%